Plant-soil feedback in the ‘real world’: how does fire fit into all of this? - Kardol, P.; Yang, T.; Arroyo, Daniel Nicolas; Teste, Francois Philippe (Springer, 2023)
Aims: Plant–soil feedback (PSF) is an important mechanism controlling plant growth, vegetation dynamics, and longer-term and larger-scale patterns of plant community diversity. We know that feedback between plants and soil biota depends on several external factors, such as nutrient and water availability, and interactions with neighbouring plants. We argue that in the ‘real world’, PSF are not working in isolation but instead proceed within a complex context of multiple interacting factors. Fire is one of those complex external factors which could greatly alter PSF by re-setting or re-directing plant-soil biota interactions. Methods: We reviewed key literature on the effects of fire on soil biota and soil physicochemical properties with soil depth, to generate predictions on the complex effects of fire on PSF. Results: We highlight that fire has strong potential to directly and indirectly affect the strength of PSF. To what extent this influences longer-term plant community trajectories depends on the interactions between fire characteristics and ecosystem type. Here, we conceptualized these effects of fire on soil properties and biota, and then discuss the main pathways through which fire should alter PSF. Conclusions: We think that PSF processes should be nullified under and after fire. Average neutral PSF responses are expected to be more common in the short-term or within the timeframe required for major soil microbial players to regain their pre-fire abundances and diversity. We conclude by providing directions for future research and possible methods to study fire effects on PSF both in the field and under controlled conditions.